2016
DOI: 10.1097/md.0000000000003317
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical Location Characteristics of Corticospinal Tract Associated With Hand Movement in the Human Brain

Abstract: The purpose of this study is to elucidate the symmetrical characteristics of corticospinal tract (CST) related with hand movement in bilateral hemispheres using probabilistic fiber tracking method.Seventeen subjects were participated in this study. Fiber tracking was performed with 2 regions of interest, hand activated functional magnetic resonance imaging (fMRI) results and pontomedullary junction in each cerebral hemisphere. Each subject's extracted fiber tract was normalized with a brain template. To measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It has been reported that there are functional and structural differences in the cerebral hemispheres of the right-and left-handed patients [4,5,10,11,16]. In corticospinal tract evaluation using DTI, asymmetry was observed to be associated with the dominant hand [12,16]. Similarly, van der Zwaag et al [18] found that lateralised hand motor movement has a greater impact on the cerebellar lobules 5 and 8 more.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that there are functional and structural differences in the cerebral hemispheres of the right-and left-handed patients [4,5,10,11,16]. In corticospinal tract evaluation using DTI, asymmetry was observed to be associated with the dominant hand [12,16]. Similarly, van der Zwaag et al [18] found that lateralised hand motor movement has a greater impact on the cerebellar lobules 5 and 8 more.…”
Section: Introductionmentioning
confidence: 95%
“…In consecutive hand movements, the corticospinal and MCP tracts work in coordination [12,15,16]. It has been reported that there are functional and structural differences in the cerebral hemispheres of the right-and left-handed patients [4,5,10,11,16].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is used to quantitatively measure the structural connectivity of white matter tracts and provide information of cellular integrity. [ 7 9 ] Decreased fractional anisotropy (FA) has been consistently proven in the affected corticospinal tract (CST) across studies in subcortical stroke involving motor pathways. [ 10 , 11 ] The resting-state functional connectivity (FC) is another widely used technique to evaluate the temporal correlations between any pair of predefined brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…A study elucidated the symmetrical characteristics of the CST in bilateral hemispheres using probabilistic ber tracking method. They clearly showed that the hand CST had symmetric structures in bilateral hemispheres [51]. When the researches emphasized different functions of the brain, especially the language, the two hemispheres are asymmetrical.…”
Section: Limitations and Expectationsmentioning
confidence: 98%